Sikap Masyarakat Mandailing Natal terhadap Gerakan Politik Fundamentalisme Kristen - Indra Harahap; Annisa Ismaida Batubara (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
ontemporary religious fundamentalism is built into plans for modernization and Western traditionalism that does not succeed against unintended signs of progress; then, at the time, his disregard for family values and principles as a social pattern was maintained by religion (Haynes, 2003). Much of the thought process is the breaking of the idea that God's work for the majority of fundamentalist gatherings is currently being undermined and replaced by specific progress manuals that lead to extremist socio-social conservative change. Other elements that support the undeniable rise of Islamic fundamentalists are; unfavorable administration, high unemployment of the population, disillusionment of the currents of modernization, the terrible consequences of the globalization project (Westernization), Western authorities and governments (European and American), urbanization, limited industrialization and the development of a confused class of the population in this regard are confused with the exhibition regime. Simply put, the declaration of Muslim political recovery that emerged in fundamentalist developments should have two verifiable roots; first, it is local: as a reaction to the social idea of the Islamic State; secondly, it is trans-public: in reaction to Western authority and globalism. As an easy road, not a few parts of today's Muslim society have decided to ride on the vehicle of Islamism which requires complete change in all parts of the general public. Keywords: People's Attitudes, Politics, Fundamentals